Bruce M. Russett: pioneer in the scientific and normative study of war, peace, and policy - Starr, Harvey (SpringerBriefs on Pioneers in Science and Practice,, 2015)
This book provides a comprehensive treatment of Russett's scientific contributions, with key examples of his major studies. It will greatly benefit today's International Relations students, deepening their understanding of the field's theory and methods. Bruce M. Russett was a founder of, and continues to be a pioneer in, the empirical analytical study of international relations and foreign policy. He has produced groundbreaking works on methodology, data collection and the application of economics to the field of international relations-especially in the area of analytical relationships between theory, policy and normative standards for morality and ethics. His body of work has clarified and furthered our understanding of peace studies by addressing power and conflict, cooperation, integration and community, democratic/Kantian peace, economic development, dependency and inequality, and the relationships between domestic and foreign politics. Russett's academic achievements and standing are the result of his bringing these areas together as a coherent entity, based on his eclectic ability to "cross boundaries" with regard to academic disciplines, sub-disciplines, methods of data gathering and analysis, and broad theoretical perspectives, as well as basic and applied research.